2015
DOI: 10.1371/journal.pntd.0004167
|View full text |Cite
|
Sign up to set email alerts
|

Formalin Inactivation of Japanese Encephalitis Virus Vaccine Alters the Antigenicity and Immunogenicity of a Neutralization Epitope in Envelope Protein Domain III

Abstract: Formalin-inactivated Japanese encephalitis virus (JEV) vaccines are widely available, but the effects of formalin inactivation on the antigenic structure of JEV and the profile of antibodies elicited after vaccination are not well understood. We used a panel of monoclonal antibodies (MAbs) to map the antigenic structure of live JEV virus, untreated control virus (UCV), formalin-inactivated commercial vaccine (FICV), and formalin-inactivated virus (FIV). The binding activity of T16 MAb against Nakayama-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 90 publications
(116 reference statements)
1
47
0
Order By: Relevance
“…It was also found that the ICE test was not able to detect and quantify proteins from inactivated Mccp with formaldehyde. This indicates that the target protein may have been degraded or that a change in conformation that could impact the epitope bound by the mAb may have occurred [35,36].…”
Section: Estimation Of Mccpmentioning
confidence: 99%
“…It was also found that the ICE test was not able to detect and quantify proteins from inactivated Mccp with formaldehyde. This indicates that the target protein may have been degraded or that a change in conformation that could impact the epitope bound by the mAb may have occurred [35,36].…”
Section: Estimation Of Mccpmentioning
confidence: 99%
“…2C). We hypothesized that this was the result of formalin fixation of R-CTB, which has been reported to alter protein structure and abrogate antigenicity (11). Therefore, we eliminated formalin fixation and turned to a live-attenuated formulation of the vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…As the endocytic-pathway intersects with antigen presentation on major histocompatibility complex (MHC) I (33) and II molecules (34), the efficiency of antigen presentation via this pathway is improved up to 10,000-fold compared phagocytosis (35,36). Formalin-inactivation abolishes MHC I presentation of measles virus (37), entry of porcine reproductive and respiratory syndrome virus (38), binding, entry, and viral RNA infectivity of polio virus (39), and modifies the antigenic structures of Japanese encephalitis virus (40). …”
Section: Discussionmentioning
confidence: 99%